Accompaniment How to Quickly Read The Bold Book (CBKG) Phase II With Qawa'id And Tarjamah Methods for Students of The Mambaul Ihsan Islamic Boarding School - Widodo, Arif; Ainak, Roihanatul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The purpose of community service activities in this form is to provide advanced basic knowledge and skills regarding procedures for reading bare books using the Qawa'id and Tarjamah methods and to foster a passion for reading bare books through CBKG. The method used uses the method in the workings of PAR (Participatory Action Research). The findings and results of this activity show that there is an increase in basic knowledge and skills greater than stage I regarding the procedure for reading bare books using the Qawa'id and Tarjamah methods on the book Fathul Mu'in and it turns out that it can also foster a passion for reading bare books.